Seni pertukangan lepa - Puteri Roslina Abdul Wahid; Ezura As'ad Azam; Dewan Bahasa dan Pustaka (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2015)
On terminology of Lepa, a Malay traditional craftmanship in Malaysia.
Includes bibliographical references (page 241-244) and index.
Keywords: Malay language -- Terminology; Boathouses -- Terminology; Boatbuilding -- Terminology; Boatbuilding -- Design and construction